(2,2'-Bipyridine-k2N,N')bis(N-isopropyl-N-methyldithiocarbamato-k2S,S')-cadmium. - Abdul Wahab, Nor Asiken; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2011)
The CdII atom in the title compound, [Cd(C5H 10NS2)2-(C10H8N 2)], exists in an N2S4 donor set defined by two chelating dithiocarbamate anions as well as a 2,2′-bipyridine ligand. The coordination geometry approximates a trigonal prism. The crystal packing features weak C-H⋯S interactions, leading to linear supramolecular chains along the a axis. The primary connections between these are by π- π stacking interactions [ring centroid distance between centrosymmetrically related pyridyl rings = 3.7455 (10) Å ]. Overall, the crystal structure may be described as comprising double layers of molecules that stack along the b axis.